I have to find the sum of the following series: $$\sum\limits_{n=1}^\infty \frac{n^3}{n!}$$

I know how to prove the convergence of this series, but how do i find the sum. I can't use the properties of derivation or integration of the series, i have to do it using the definition that a series converges iff it's sequence of partial sum converges.

up vote 5 down vote accepted

Expanding on @Winther's comment, you may write

$$ \begin{align} \sum_1^{\infty} \frac{n^3}{n!}&=\sum_1^{\infty} \frac{n (n - 1) (n - 2) + 3 n (n - 1) + n}{n!}\\\\ &=\sum_3^{\infty} \frac{n (n - 1) (n - 2)}{n!}+3\sum_2^{\infty} \frac{n(n - 1) }{n!}+\sum_1^{\infty} \frac{n}{n!}\\\\ &=\sum_3^{\infty} \frac{1}{(n-3)!}+3\sum_2^{\infty} \frac{1}{(n-2)!}+\sum_1^{\infty} \frac{1}{(n-1)!}\\\\ &=\sum_0^{\infty} \frac{1}{n!}+3\sum_0^{\infty} \frac{1}{n!}+\sum_0^{\infty} \frac{1}{n!}\\\\ &=5e \end{align} $$

since $$ \sum_0^{\infty} \frac{x^n}{n!}=e^x, \quad x \in \mathbb{C}. $$

In general, if

$$f(z) = \sum_{n=0}^{\infty} a_n z^n$$

Then

$$\sum_{n=1}^{\infty} n^3 a_n z^n = \frac{d}{dz} \left [z \frac{d}{dz} \left [z \frac{d}{dz} f(z) \right ]\right ]$$

In your case $a_n = 1/n!$ implies that $f(z) = e^z$. Take the derivatives, set $z=1$. The result is

$$\sum_{n=0}^{\infty} \frac{n^3}{n!} = 5 e$$

  • How can one find $f$ forn $a_n$? Just curious, if it is long, I'll ask a question about it. – wythagoras Oct 26 '15 at 17:22
  • @wythagoras: Well, it helps to be familiar with some basic Taylor series, such as that for $e^z$. – Ron Gordon Oct 26 '15 at 17:23
  • Thank you for the tip, but as I said I can't use derivatives or integrals, because in this curse I'm learning only the basics (Analysis 1), in Analysis 2 I learn derivatives and integrals, so that is the main problem... – zermelovac Oct 26 '15 at 17:24
  • Then you may want to read the comment from @Winther. Again, that assumes you know how to recognize a famous series for $e$. – Ron Gordon Oct 26 '15 at 17:26

The other answers have given you different ways to solve the problem at hand. I will below just add some notes on how one can evaluate general sums on the form $\sum_{n=0}^\infty \frac{n^k}{n!}$ where $k$ is any integer using just algebraic manipulations (since you said you cannot use derivatives). I'm however assuming we already know that $\sum_{n=0}^\infty\frac{1}{n!} = e$.

We start by noting that we can always write $n^k$ on the form

$$n^k = C_1n + C_2n(n-1) + \ldots + C_kn(n-1)\cdots(n-k+1) \equiv \sum_{j=1}^{k} C_j{n\choose j}j!$$

where $C_i$ are some real numbers (see below for a simple algorithm to compute these numbers). For example

$$n^2 = n(n-1) + n$$ and $$n^4 = n(n-1)(n-2)(n-3) + 6 n (n - 1) (n - 2) + 7 n (n - 1) + n$$

The reason this form is useful is that we can very easily evaluate the sums

$$\sum_{n=0}^\infty\frac{n(n-1)\cdots(n-i)}{n!} = \sum_{n=i+1}^\infty \frac{1}{(n-i-1)!} = \sum_{m=0}^\infty \frac{1}{m!} = e$$

where we have simply shifted the summation index to $m = n-i-1$ in the last step. The sum above does not depend on $i$ at all so the sum we are after becomes

$$\sum_{n=0}^\infty \frac{n^k}{n!} = \sum_{n=0}^\infty \frac{ C_1n + C_2n(n-1) + \ldots + C_kn(n-1)\cdots(n-k+1)}{n!} \\= C_1 e + C_2 e + \ldots + C_k e = \left(\sum_{j=1}^k C_j\right) e$$

so the problem reduces to finding the $C_i$'s.


Here is a simple method to compute the $C_i$'s. Lets take $k=3$ as an example and start by writing $$n^3 = \color{blue}{1}n^3$$ Now we subtract $\color{blue}{1}n(n-1)(n-2)$ to get $$n^3 - \color{blue}{1} n(n-1)(n-2) = \color{red}{3} n^2 - 2n$$ so $C_2 = \color{red}{3}$. Now subtract $\color{red}{3}n(n-1)$ to get $$n^3 - n(n-1)(n-2) - \color{red}{3}n(n-1) = \color{pink}{1} n$$ so $C_1 = \color{pink}{1}$. We have now shown that $$n^3 = \color{blue}{1}n(n-1)(n-2) + \color{red}{3}n(n-1) + \color{pink}{1} n$$ so using the formula above we have $$\sum_{n=0}^\infty \frac{n^3}{n!} = (\color{blue}{1}+\color{red}{3}+\color{pink}{1})e = 5e$$


If you want to read more about this, the numbers $C_j$ are the so-called Stirling numbers of the second kind, $C_j \equiv S(k,j)$, and the sum $\sum_{j=1}^k C_j = \sum_{j=1}^k S(k,j) \equiv B_k$ are the so-called $k$'th Bell number (and is always an integer). Using this the final result can be compactly written

$$\sum_{n=0}^\infty \frac{n^k}{n!} = eB_k$$

which is known as Dobinski's formula. Knowing this there exist an even simpler method to compute the Bell numbers using a "Pascal's triangle" approach, see for example this page.

Your Answer

By clicking "Post Your Answer", you acknowledge that you have read our updated terms of service, privacy policy and cookie policy, and that your continued use of the website is subject to these policies.

Not the answer you're looking for? Browse other questions tagged or ask your own question.